Transforming Viewpoints: To Mix Metaphors in the Field of Painting - Schilo, Ann; Sabadini, Anna (Common Ground Publishing, 2010)
Visual art has the capacity to not only change the way a person sees the world but also how she might interpret and understand her engagement with the surrounding culture and environment. For the artist, this transformation manifests itself through the daily practice of art making from the rituals of studio, with its intensity of focus on visualisation, to the archive of conceptual concerns where ideas, theoretical frameworks and the histories of art conjoin their voices to underpin the works in progress. For the viewer, the resultant artwork has a propensity to reveal alternative ways of appreciating her everyday life. Weaving together ideas drawn from diverse fields such as feminist aesthetics, philosophy, geography and art history, this paper seeks an understanding of the various dimensions of artistic transformation. Through an investigation of the work of Western Australian artist/scholar, Anna Sabadini and her use of metaphors in painting, it proposes a way of perceiving that subverts the authority of the gaze offering viewpoints that destabilise established binaries and conventional categorizations.